2020
DOI: 10.1186/s12891-020-03217-1
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of osteoporosis among 368 residents in China: a cross-sectional study

Abstract: Background: Studies on osteoporosis awareness among the general population in China are still limited. We examined the level of osteoporosis awareness among residents in China, determined the risk factors associated with a lower level of osteoporosis awareness, and assessed the sources of their knowledge about osteoporosis. Methods: We conducted a cross-sectional study among 368 general residents aged 30 years or older from 19 provinces during January-March 2018 in China. All participants were identified and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…Compared to other countries such as China (67.8%) and Malaysia (87.1%), the proportion of female patients with good osteoporosis knowledge in this study was low (11.7%) [11,14]. This was also markedly lower than the previous local study performed 2 decades ago which showed that 57.3% had good osteoporosis awareness.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Compared to other countries such as China (67.8%) and Malaysia (87.1%), the proportion of female patients with good osteoporosis knowledge in this study was low (11.7%) [11,14]. This was also markedly lower than the previous local study performed 2 decades ago which showed that 57.3% had good osteoporosis awareness.…”
Section: Discussioncontrasting
confidence: 77%
“…The levels affecting osteoporosis-related knowledge are known to vary across countries, study designs, and types of study participants recruited [13,14]. For example, a study in Pakistan showed that only 8% of participants had a good level of osteoporosis knowledge [13,14]. In contrast, a study conducted in China showed that the overall osteoporosis awareness was 67.8% [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also found that the knowledge of osteoporosis in postmenopausal women diagnosed with the disease was limited [32][33][34], and level of education was a strong predictor of knowledge [34,35]. In China, Oumer et al [36] found that the awareness levels for osteoporosis were moderate; lower family income and education level were risk factors for lower awareness. A community-based survey in Saudi Arabia found that women with a low level of education and who had a history of fractures were at high risk of low bone mineral density (BMD) [37].…”
Section: Discussionmentioning
confidence: 97%
“…Osteoporosis is a severe medical condition that mainly affects older female population and is characterized by low bone mass density resulting in bone porosity and fragility [1,2]. The prevalence of this disease increases with population aging, and it is becoming a worldwide challenge of elderly health [3]. The risk of fractures rises markedly as it gets worse [4].Osteoporotic fractures are frequently identi ed in thoracic and lumbar spine even after a slight trauma, presenting with back megalgia, kyphosis, compromised mobility, as well as high mortality [2].…”
Section: Introductionmentioning
confidence: 99%